2002
DOI: 10.1136/oem.59.11.759
|View full text |Cite
|
Sign up to set email alerts
|

Are women more sensitive than men to 2-propanol andm-xylene vapours?

Abstract: Aims: To evaluate possible differences between men and women in acute health effects after controlled short term chamber exposure to vapours of two common organic solvents. Methods: Fifty six healthy volunteers (28 per sex) were exposed to 150 ppm 2-propanol, 50 ppm m-xylene, and clean air for two hours at rest. The subjects rated symptoms on a visual analogue scale before, during, and after the exposure. Blinking frequency was measured continuously during exposure. Pulmonary function, nasal swelling, inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 27 publications
1
46
0
6
Order By: Relevance
“…We found no previous study on associations between exposure to xylene in schools and fatigue. However, one exposure chamber study found an increase of fatigue after exposure to mxylene but at much higher levels (50 ppb for 2 h) (Ernstgård et al, 2002). We found that indoor methylcyclohexane measured during class was negatively associated with rhinitis.…”
Section: Discussionmentioning
confidence: 54%
“…We found no previous study on associations between exposure to xylene in schools and fatigue. However, one exposure chamber study found an increase of fatigue after exposure to mxylene but at much higher levels (50 ppb for 2 h) (Ernstgård et al, 2002). We found that indoor methylcyclohexane measured during class was negatively associated with rhinitis.…”
Section: Discussionmentioning
confidence: 54%
“…Die Symptome waren insgesamt schwach ausgeprägt und erreichten einen Wert von 14,9 auf einer Skala von 0 bis 100, das entspricht einer verbalen Graduierung von etwas mehr als "kaum". Frauen waren etwas sensibler bezüglich der subjektiven Wahrnehmung einer reizenden Wirkung als Männer (Ernstgård et al 2002).…”
Section: Einmalige Expositionunclassified
“…In einer weiteren Untersuchung wurden je 28 Männer und Frauen 2 h lang gegenüber 220 mg m-Xylol/m 3 exponiert [45]. Es wurden sowohl subjektive Eindrücke (anhand einer visuellen Analogskala) als auch objektive Parameter wie Lungenfunktion, nasale Schleimhautschwellung, Entzündungsmarker in der nasalen Lavage und die Fähigkeit zur Farbdifferenzierung untersucht.…”
Section: Irritative Wirkungenunclassified
“…In der Gesamteinschät-zung wurde die Expositionskonzentration von 220 mg/m 3 als "minimale LOAEC" eingestuft. Lungenfunktionswerte (FVC, FEF 75 ) waren bei Frauen 3 h nach Expositionsende minimal (< 4 %) vermindert, alle anderen Parameter waren bei Männern und Frauen unmittelbar im Anschluss an die Exposition und 3 h später nicht verändert [45].…”
Section: Irritative Wirkungenunclassified